Rancang Bangun Alat Uncoiler Cutting Plat Strip - Purwa Bimantara; Tri Andi Setiawan; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Outdoor Furniture Company is a company engaged in the manufacturing industry that produces goods according to orders received. In the production process, one of the orders currently being produced is found a condition that makes the production process not effective, namely the process of preparing raw materials which is still done manually. Therefore, this research was carried out by making a design for an uncoiler as well as being useful as a cutter for the process of preparing raw materials. The method used in this research is the Ulrich method, where this method consists of the stages of the development process to get the best design as needed. Based on the results of design, manufacture, and testing, an uncoiler cutting plate strip is produced as a tool for one of the manufacturing processes for cutting strip plate material. This tool is designed using Fusion 360 software and the Ulrich method for selecting the best concept from 3 existing concepts. After testing, this tool is able to cut strip plate material with various dimensions according to the plan and has a precision level under 5 mm, and is able to cut at a speed of less than 38 seconds, which means this tool is better than existing products in the company.